Understanding grain yield responses to source-sink ratios during grain filling in wheat and barley under contrasting environments - Serrago, Roman Augusto (2013)
A better understanding of the effects of different source?sink ratio during the grain filling period on grain growth may be relevant in order to further increase cereal grain yield. The main objective of the present work was to determine the effect of different manipulations of the source?sink ratios in wheat and barley grown at four different environmental conditions on responsiveness of sinks (grain growth and yield) and sources (spike photosynthesis and water soluble carbohydrates in the stems). Four treatments were imposed 7 days after anthesis in two contrasting locations with low- and high-inputs conditions in wheat (cv. Soissons) and barley (cv. Sunrise): they were a control, a treatment removing all the spikelets from the upper half of the spikes (TS), and shadings decreasing incident radiation by 75% on the whole canopy (SW) or only on the leaves (having the top area of the meshes individual holes for each spike to be exposed to solar radiation, SL). As expected grain yield was closely related to grain number per m2. Average grain weight was reduced by shading treatments far more markedly in Sw than in SL. Interestingly, significant amounts of water soluble carbohydrates in the stems remained at maturity in SL and Sw treatments and spike photosynthesis in SL was consistently higher than in the unshaded controls in both species. These results may be an indication that wheat and barley are not source-limited during grain filling and that only when subjected to an extremely severe stress, grain size would be reduced due to lack of enough assimilates available to fill them.